Images of God in Toba Batak storytelling - Angerler, Johann (UI Scholars Hub, 2016)
This paper examines the ways in which God the Creator, the High God, is described in Toba Batak folk-tales. The sources for this investigation are stories recorded in pre-colonial (around 1850), colonial and post-colonial times (up to 2014). In different stories the High God can appear under various names, forms and gender, and resides in various places never inhabited by humans. Unlike a Deus otiosus, the Toba Batak High God is not